Housing Consumption and Urbanization - Lozano-Gracia, Nancy; Young, Cheryl (World Bank Group, Washington, DC, 2014)
Rapid urbanization in Sub-Saharan Africa places immense pressure on urban services to meet the needs of the burgeoning urban population. Although several country- or city-level reports offer insight into the housing challenges of specific places, little is known about regional patterns affecting housing markets. This lack of clear knowledge on the relative importance of the factors influencing households' housing demand in countries in Sub-Saharan Africa inhibits policy makers, researchers, the private sector, and development partners from making informed decisions when addressing affordable housing provision and the rapid increase in and growth of informal settlements. To shed light on the contours of housing patterns and impediments impacting the region's households, this paper provides a systematic review of housing conditions in Sub-Saharan Africa. By drilling down into the housing issues in the region from the perspective of the household, the paper analyses the trade-offs households make in allocating their budgets over time to housing and other amenities and provides a first approximation at understanding the differences in households' expenditure patterns and housing decisions across countries. The findings suggest that rather than emphasizing policies that purport to increase expenditures on housing at this stage of development, policy makers in Sub-Saharan Africa should focus on extending access to basic services and strengthening coordination between land use planning and service provision. As incomes increase, this focus would allow households the opportunity to access houses that are equipped with basic infrastructure and help countries move toward better overall quality of housing.